PENGARUH PADAT TEBAR TERHADAP KANDUNGAN ZAT GIZI IKAN LELE YANG DIPELIHARA DENGAN TEKNOLOGI BIOFLOK - Anang Suhardianto; Ariyanti Hartari (Jurnal Matematika Sains dan Teknologi, 2019)
This study aims to determine the effect of stocking density on the nutrient content of catfish that is cared with biofloc technology. Nutrients observed: 1) water content, 2) protein, 3) carbohydrates, 4) total fat, 5) saturated fatty acids / SFA, 6) monounsaturated fatty acids/ MUFA, 7) plural unsaturated fatty acids / PUFA , 8) omega-3, 9) omega-6, and 10) omega 9. Statistical tests on the 10 variables showed that stocking density did not have a significant effect on the 10 variables at a 5% confidence interval. Stocking density of treatment is 1000 heads/pond (T1), 2000 heads/pond (T2), 3000 heads/pond (T3), with a pond size of 2.0 m x height 1.0 m. Research results: 1. The average water content is 69.40–71.47% and the highest T3. 2. The protein content is 14.70-15.90%, the highest T2. 3. Carbohydrate content of 5.16-5.50%, the highest T2. 4. The average total fat content of 6.73-7.78%, the highest T1. 5. SFA content is around 43%, PUFA around 23%, and MUFA around 32%. 6. The highest omega-3 content is T3, then T1, and T2. Omega-6 and 9 sequence contents are T1, T2, and T3. It was concluded, the treatment of biofloc catfish stocking densities at a 5% confidence interval did not have a significant effect on the specified nutrient content. Penelitian ini bertujuan untuk menentukan pengaruh padat tebar terhadap kandungan zat gizi ikan lele yang dipelihara dengan teknologi bioflok. Zat gizi yang diamati: 1) kandungan air, 2) protein, 3) karbohidrat, 4) lemak total, 5) asam lemak jenuh/SFA, 6) asam lemak tak jenuh tunggal/MUFA, 7) asam lemak tak jenuh jamak/PUFA, 8) omega-3, 9) omega 6, dan 10) omega 9. Uji statistik terhadap ke-10 variabel menunjukkan padat tebar tidak memberikan pengaruh nyata terhadap ke-10 variabel pada selang kepercayaan 5%. Padat tebar perlakuan adalah 1000 ekor/kolam (T1), 2000 ekor/kolam (T2), 3000 ekor/kolam (T3), dengan ukuran kolam diameter 2,0 m x tinggi 1,0 m. Hasil penelitian: 1. Rata-rata kandungan air 69,40–71,47% dan T3 tertinggi. 2. Kandungan protein 14,70–15,90%, T2 tertinggi. 3. Kandungan karbohidrat 5,16–5,50%, T2 tertinggi. 4. Rata-rata kandungan lemak total 6,73–7,98%, T1 tertinggi. 5. Kandungan SFA sekitar 43%, PUFA sekitar 23%, dan MUFA sekitar 32%. 6. Kandungan omega-3 tertinggi T3, kemudian T1, dan T2. Omega-6 dan 9 urutan kandungannya T1, T2, dan T3. Disimpulkan, perlakuan padat tebar lele bioflok pada selang kepercayaan 5% tidak memberikan pengaruh yang nyata terhadap kandungan zat gizi yang ditentukan.